0069 Knee disorders, work limitations and work status. first results from the constances cohort. (21st August 2017) - Descatha, Alexis; Kuijer, Paul; Dale, Ann-Marie; Petit, Audrey; Frings-Dresen, Monique; Evanoff, Bradley A; Leclerc, Annette; Roquelaure, Yves
Abstract : Objective: Knee disorders, including osteoarthritis and knee replacement, are a growing problem for more and more workers due to increasing retirement ages. Aim is to describe work-related outcomes of possible knee replacement, meniscal surgery and other knee pain in a new large population cohort at its inception. Methods: The CONSTANCES cohort is a randomly selected representative sample of French adults aged 18–69 years at recruitment. Participants completed symptom questionnaires, and surgery in the last 4 years period was collected from a national health claims database. Knee disorders were defined as severe or daily knee pain, or history of surgery for meniscal tear or knee replacement. We considered several outcomes, including self-reported functional limitations (climbing stairs, walk 1 km, carrying 5 kg), task modifications and current work status. Multinomial logistic models were built separately for men and women; only variables with an Odds Ratio >2 (or <0.5) at p<0.001 were considered significant after adjustment for other relevant variables. Results: Of 85.826 participants, of whom 38.571 (44.9%) reported knee pain. 10.683 (12.4%) reported severe knee pain, 1305 (1.5%) with meniscal tear surgery, and 403 (0.5%) with knee replacement. All limitations considered were significantly associated with severe knee pain, meniscus surgery and knee replacements among men and women, such as task modification for knee disorders. Loss of activity was only significantly associated with knee replacement among men. Conclusions: Based on a cross-sectional design at this time, theses first analyses reported a poor outcomes of knee disorders for work-related activities.